Investigation of various factors affecting methylene blue adsorption on agricultural waste: Banana stalks - Mahadlek, Jongporn; Mahadlek, Jongjan (Science, Engineering and Health Studies, 2020)
Banana stalks are interesting agricultural waste products that can be utilized to eliminate dyes from textile wastewater because it is a low cost adsorbent and a readily available resource in Thailand. This study investigated the effect of various factors on methylene blue (MB) adsorption on different sizes of dried banana stalks. Before and after MB adsorption, banana stalks were characterized using Fourier transform infrared spectroscopy, scanning electron microscopy, and powder X-ray diffraction. The factors that were investigated included adsorbent amount, contact time, shaking speed, and initial MB dye concentration. The adsorption profile was identified using the Langmuir and Freundlich isotherms. Results indicated that all factors affected the MB adsorption of banana stalks. The highest MB adsorption percentage was observed in banana stalks ranging in size from 0.18 mm to 0.25 mm (40-60 mesh (S)), followed by those ranging in size from 0.25 mm to 0.40 mm (60-80 mesh (M)) and from 1.0 cm to 1.5 cm. The equilibrium data of these three sizes of banana stalks fitted well to the Freundlich model. These results confirmed that the adsorption profile was multilayered and occurred through physicochemical interactions. The most suitable adsorption kinetics model was the pseudo-second-order kinetics model. Therefore, these data can be used as a reference in establishing an alternative method for removing various dyes from wastewater using low cost eco-friendly agricultural waste.